Immunology in Malaysia--a review. - Bosco, J. (1988)
Immunology is a discipline that traverses all branches of clinical medicine. Thus since about ten years ago major hospitals in Malaysia established routine clinical immunology services particularly in the diagnosis of autoimmune/connective tissue disorders. More recently these laboratories have ventured into basic research in Dengue Haemorrhagic Fever, Leukaemia Immunology, Nasopharyngeal Cancer and Leprosy. The rationale for these projects together with early results from them are discussed.